2004
DOI: 10.1103/physrevlett.93.153003
|View full text |Cite
|
Sign up to set email alerts
|

Kerr Effect in Liquid Helium at Temperatures Below the Superfluid Transition

Abstract: The electro-optical Kerr effect induced by a slowly-varying applied electric field in liquid helium at temperatures below the λ-point is investigated. The Kerr constant of liquid helium is measured to be (1.43±0.02 (stat) ±0.04 (sys) )×10 −20 (cm/V) 2 at T = 1.5 K. Within the experimental uncertainty, the Kerr constant is independent of temperature in the range T = 1.5 K to 2.17 K, which implies that the Kerr constant of the superfluid component of liquid helium is the same as that of normal liquid helium. Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In 2004 a measurement of the Kerr constant K exp was reported for the superfluid helium in the temperature range 1.5-2.17 K [40]. The measured value of K exp = (1.43 ± 0.06) × 10 −20 (cm/V) 2 can be compared with our calculations.…”
Section: Comparison With the Experimental Datasupporting
confidence: 57%
“…In 2004 a measurement of the Kerr constant K exp was reported for the superfluid helium in the temperature range 1.5-2.17 K [40]. The measured value of K exp = (1.43 ± 0.06) × 10 −20 (cm/V) 2 can be compared with our calculations.…”
Section: Comparison With the Experimental Datasupporting
confidence: 57%
“…The polarized 3 He slowly depolarizes in the storage chamber and must be periodically replenished: the low temperature dynamics of 3 He motion in superfluid 4 He makes this possible, and unpolarized test measurements have been performed [176,177]. One obtains d n by measuring the difference in the neutron and 3 He precession frequencies for the different orientation of the electric field, which can be measured optically in superfluid helium using the Kerr effect [178].…”
Section: Electric Dipole Moment Experimentsmentioning
confidence: 99%
“…In a practical experimental setup, we expect Kerr effect signals of the order of 10 −5 -10 −6 rad. 1 In our laboratory, where low-temperature optical access is implemented with a set of 1-in.-diameter, 2-mm-thick, epoxy-mounted fused-silica windows, testing with 632 nm light showed that window birefringence introduces offsets in polarization rotation and ellipticity, the latter being defined as inverse tangent of ratio of the axes of the polarization ellipse, on the order of 0.1 rad, which also depend on the window temperature. This offset drifts within a range of about 10 −4 rad over periods of hundreds of seconds, and this noise overwhelms the typical signal from the Kerr effect of liquid helium.…”
Section: Introductionmentioning
confidence: 99%
“…11 In other experiments, notably Kerr effect experiments, modulation of the applied electric field is used to distinguish the signal from background noise. 1 Neither of these methods can be used in the application of Kerr effect for monitoring electric fields. Thus, we explore the feasibility of measuring and compensating for the optical-window birefringence drifts using the reflected light from the last optical surface before the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation